Точка звороту в системі диференціальних рівнянь з аналітичним оператором - Бобочко, В.М. (Український математичний журнал, 1996)
We construct uniform asymptotics for a solution of a system of singularly perturbed differential equations with turning point. We consider the case where the boundary operator analytically depends on a small parameter.